Physical Quality of Red Chili Powder (Capsicum Annum L.) Result - Dian Purbasari; Rike Risdiyanti Eka Putri (Universitas Muhammadiyah Mataram, 2021)
One of the horticultural commodities that are rapidly damaged is red chili. Red chili is one type of vegetable that has fairly high water content. As a result of the high water content, red chilies are easily wilted and rotted. One alternative is through the drying process of fresh red chilies into chili powder using the foam-mat drying method. The purpose of this study was to determine the physical quality of red chili powder with a combination of variations in drying temperature and developer dosage. The results of this study showed that at a drying temperature of 80°C and a 5% developer dose, the fastest drying time was 7-8 hours with the lowest moisture content being 8.44%. The highest yield value (9.08%) was at a drying temperature of 60°C; the value of the degree of fineness (FM) is 0.601; the value of the brightness level (L) is 51.95; the value of yellowness level (b) is 24.26; and the bulk density value is 0.495 g/ml. The highest value of grain size (D) at a drying temperature of 80°C is 0.00512 mm; the value of the level of redness (a) is 30.91; the value of water absorption (DSA) is 2.73 g/ml; and oil absorption (DSM) is 1.23 g/ml